Abdominal liposuction: evolving from high to medium definition - Rogerio Schützler Gomes; Gabriela Valente Nicolau (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: Currently, the concept of high-definition liposuction (HDL or HD Lipo) is increasingly accepted. However, we noticed patients' search for results with not-sovigorous marking, especially in the abdominal region, what we have called medium-definition liposuction or MD Lipo. This study aims to present a series of clinical cases performed by the MD Lipo technique, using the conventional liposuction method. Methods: Retrospective study where patients underwent liposuction to obtain abdominal definition under the linea alba, semilunaris and tendinous intersections. We use cylindrical and malleable silicone tubes in the dressing. Results: One hundred and seven cases were included, of which 85 completed the 6-month follow-up. After 6 months, the results were considered good by all patients and medical staff. Discussion: The concept of HD Lipo is recent and has been receiving increasing acceptance. The search for more natural and smooth results led to developing the term medium or moderate definition liposuction (MD Lipo). We believe that every plastic surgeon can perform this additional abdominal definition finish with his preferred method of liposuction, either low energy (syringe, liposuction device and vibroliposuction device) or high energy (laser liposuction or ultrasonic liposuction). We can use silicone tubes to better adherence of the skin to aponeurosis and better define the grooves formed. Conclusion: The technique of medium definition abdominal liposuction (MD Lipo) has been described, using the conventional method of liposuction, in the alba and semilunaris lines and the tendinous intersections of the rectus abdominis muscle.